Concerns and expectations in women with polycystic ovary syndrome vary across age and ethnicity: findings from PCOS Pearls Study - Elghobashy, Mirna; Lau, Gar Mun; Davitadze, Meri; Gillett, Caroline D. T.; O’Reilly, Michael W.; Arlt, Wiebke; , PCOS SEva Working Group; Lindenmeyer, Antje; Kempegowda, Punith (Frontiers in Endocrinology, 2023)
Objective: To understand and explore the perceptions and opinions of women with polycystic ovary syndrome (PCOS) and further delineate the variations across age and ethnicity. Design: Qualitative survey focussed on lived experiences of people with PCOS. Participants could share their views either as written text or as voice note audio recording(s) on WhatsApp. The data from the audio were transcribed verbatim. Responses were coded by two study members independently, using a thematic inductive method with NVivo 12. Two senior study members then reviewed these codes to identify common themes. Subjects: Women with PCOS aged 18-60 years. Results: 43 of 45 participants had a formal diagnosis of PCOS, the remaining two had suspected PCOS which was under investigation. Four participants opted to share their views as voice note recordings. Poor mental health was the most reported (83.3% of participants), followed by dermatological (81.0%) and menstrual issues (76.2%). Participants were generally dissatisfied with the care they received (88.1%). A lengthy diagnostic journey was reported in 35.7% of cases. 52.6% felt less feminine, particularly with regard to weight gain and infertility. As part of the recommendations by participants, it was emphasised that others with the condition should educate themselves and be proactive in their management. 46.3% reported that being more enlightened regarding their condition improved their health outcomes and enabled them to advocate for their own care. Women in their 20s expressed distress due to poor mental health, needing a longer time to get the diagnosis, and having weight and eating concerns. While women with PCOS in their 30s discussed their menstrual irregularities and Fertility issues, those in their 40s expressed their concerns about the societal expectations of women when diagnosed with PCOS. The concerns varied across ethnicities as well. Conclusion: PCOS has wide-ranging consequences for women living with the condition, with many dissatisfied with the clinical support they currently receive. The concerns and expectations vary across ages and ethnicities. Therefore, we propose involving women with PCOS to co-create clinical and educational resources informed by lived experiences to provide end-user-informed services.